1answer.
Ask question
Login Signup
Ask question
All categories
  • English
  • Mathematics
  • Social Studies
  • Business
  • History
  • Health
  • Geography
  • Biology
  • Physics
  • Chemistry
  • Computers and Technology
  • Arts
  • World Languages
  • Spanish
  • French
  • German
  • Advanced Placement (AP)
  • SAT
  • Medicine
  • Law
  • Engineering
ch4aika [34]
3 years ago
8

How do you solve a quadratic equation

Mathematics
2 answers:
MAXImum [283]3 years ago
5 0
<span>You should already know how to factor quadratics. (If not, review Factoring Quadratics<span>.) The new thing here is that the quadratic is part of an equation, and you're told to solve for the values of </span>x<span> that make the equation true. Here's how it works: </span></span>Solve (x – 3)(x – 4) = 0. Okay, this one is already factored for me. But how do I solve this?Think: If I multiply two things together and the result is zero, what can I say about those two things? I can say that at least one of them must also be zero. That is, the only way to multiply and get zero is to multiply by zero. (This is sometimes called "The Zero Factor Property" or "Rule" or "Principle".) Warning: You cannot make this statement about any other number! You can only make the conclusion about the factors ("one of them must equal zero") if the product itself equals zero. If the above product of factors had been equal to, say, 4, then we would still have no idea what was the value of either of the factors; we would not have been able (we would not have been mathematically "justified") in makingany claim about the values of the factors. Because you can only make the conclusion ("one of the factors must have equaled zero") if the product equals zero, you must always have the equation in the form "(quadratic) equals (zero)" before you can attempt to solve it.  The Zero Factor Principle tells me that at least one of the factors must be equal to zero. Since at least one of the factors must be zero, I'll set them eachequal to zero:<span><span>x – 3 = 0</span><span>   or   </span><span>x – 4 = 0</span></span><span><span>This gives me simple linear equations, and they're easy to solve:</span></span><span><span>x = 3</span><span>  or  </span><span>x = 4</span></span><span><span>And this is the solution they're looking for:  </span>x = 3, 4</span><span>Note that "<span>x = 3, 4</span>" means the same thing as "<span>x = 3</span><span>  or  </span><span>x = 4</span>"; the only difference is the formatting. The "<span>x = 3, 4</span>" format is more-typically used.</span><span><span>One important issue should be mentioned at this point: Just as with linear equations, the solutions to quadratic equations may be verified</span><span> by plugging them back into the original equation, and making sure that they work, that they result in a true statement. For the above example, we would do the following:</span></span><span><span> </span></span><span><span>Checking </span><span>x = 3</span><span> in </span><span>(x – 3)(x – 4) = 0</span>:</span><span>([3] – 3)([3] – 4) ?=? 0 <span>
     (3 – 3)(3 – 4) ?=? 0</span> <span>
               (0)(–1) ?=? 0</span> <span>
                       0   =   0</span></span><span><span>Checking </span><span>x = 4</span><span> in </span><span>(x – 3)(x – 4) = 0</span>:</span><span>([4] – 3)([4] – 4) ?=? 0 <span>
     (4 – 3)(4 – 4) ?=? 0</span> <span>
                 (1)(0) ?=? 0</span> <span>
                       0   =   0</span></span>So both solutions "check" and are thus verified as being correct.<span>Solve </span><span>x2 + 5x + 6 = 0</span>.<span><span>This equation is already in the form "(quadratic) equals (zero)" but, unlike the previous example, this isn't yet factored. The quadratic must first be factored, because it is only when you MULTIPLY and get zero that you can say anything about the factors and solutions. You can't conclude anything about the individual terms of the unfactored quadratic (like the </span><span>5x</span><span> or the </span>6), because you can add lots of stuff that totals zero.</span>So the first thing I have to do is factor:<span>x2 + 5x + 6 = (x + 2)(x + 3)</span>Set this equal to zero:<span>(x + 2)(x + 3) = 0</span><span>Solve each factor: Copyright © Elizabeth Stapel 2002-2011 All Rights Reserved</span><span><span><span>x + 2 = 0  </span>or<span>  x + 3 = 0</span></span><span> 
</span><span><span>x = –2</span><span>  or  </span><span>x = – 3</span></span></span><span>The solution to </span><span>x2 + 5x + 6 = 0</span><span> is </span><span>x = –3, –2</span><span><span>Checking </span><span>x = </span>–3<span> and</span> <span>x = </span><span>–2 </span><span>in </span><span>x2 + 5x + 6 = 0:</span></span><span><span>[–3]2 + 5[–3] + 6 ?=? 0</span> <span>
           9 – 15 + 6 ?=? 0</span> <span>
           9 + 6 – 15 ?=? 0</span> <span>
               15 – 15 ?=? 0</span> <span>
                        0   =   0</span></span><span><span>[–2]2 + 5[–2] + 6 ?=? 0</span> <span>
           4 – 10 + 6 ?=? 0</span> <span>
           4 + 6 – 10 ?=? 0</span> <span>
               10 – 10 ?=? 0</span> <span>
                        0   =   0</span></span>So both solutions "check".<span>Solve </span><span>x2 – 3 = 2x</span>.This equation is not in "(quadratic) equals (zero)" form, so I can't try to solve it yet. The first thing I need to do is get all the terms over on one side, with zero on the other side. Only then can I factor and solve:<span><span>x2 – 3 = 2x</span><span> 
</span><span>x2 – 2x – 3 = 0</span><span> 
</span><span>(x – 3)(x + 1) = 0</span><span> 
</span><span><span>x – 3 = 0  </span>or<span>  x + 1 = 0</span></span><span> 
</span><span><span>x = 3  </span>or<span>  x = –1</span></span></span><span>Then the solution to </span><span>x2 – 3 = 2x</span><span> is </span><span>x = –1, 3</span><span>Solve </span><span>(x + 2)(x + 3) = 12</span>.It is very common for students to see this type of problem, and say:"Cool! It's already factored! So I'll set the factors equal to 12 and 
solve to get x = 10 and x = 9. That was easy!"<span><span>Yeah, it was easy; it was also (warning!) wrong. </span><span><span>Besides the fact that </span>(10 + 2)(9 + 3)<span> does not equal </span>12, you should never forget that you must have "(quadratic) equals (zero)" before you can solve.</span></span><span><span>So, tempting though it may be, I cannot set each of the factors above equal to the other side of the equation and "solve". Instead, I first have to multiply out and simplify the left-hand side, then subtract the </span>12<span> over to the left-hand side, and re-factor. Only then can I solve.</span></span><span><span>(x + 2)(x + 3) = 12</span><span> 
</span><span>x2 + 5x + 6 = 12</span><span> 
</span><span>x2 + 5x – 6 = 0</span><span> 
</span><span>(x + 6)(x – 1) = 0</span><span> 
</span><span><span>x + 6 = 0  </span>or<span>   x – 1 = 0</span></span><span> 
</span><span><span>x = –6  </span>or<span>   x = 1</span></span></span><span>Then the solution to </span><span>(x + 2)(x + 3) = 12</span><span> is </span><span>x = –6, 1</span>
PilotLPTM [1.2K]3 years ago
4 0
- \beta +- \sqrt{ \beta }  {2} -4ac (all divided by)/2a
You might be interested in
Seven less than a number is 18
kherson [118]
X-7=18
+7 to both side
X=25
5 0
2 years ago
Which expression is equivalent to 6+4.5(32f-14f)
vichka [17]

Answer:

6 + 4.5(32f - 14f) = 6 + 81f

Step-by-step explanation:

Let us apply the distributive property to find an equivalent expression for:

6  + 4.5(32f - 14f)

For all real numbers a, b, and c, the distributive property says that:

a(b + c) = ab + ac

We apply this property to get:

6 + 4.5(32f - 14f) = 6 + 4.5 \times 32f  + 4.5 \times  - 14f

6 + 4.5(32f - 14f) = 6 + 144f   - 63f

We simplify the RHS to get:

6 + 4.5(32f - 14f) = 6 + 81f

8 0
3 years ago
Can’t figure out how to figure out the diameter from the area..... Btw look at the image
julia-pushkina [17]

Answer:

2.26 in

Step-by-step explanation:

Given:  the area of the slice is 4 in^2.

The formula for the area of a circle is A = (pi)(r)^2, where r is the radius.

Therefore,

A = 4 in^2 = (pi)(r^2), or

   

         4 in^2

r^2 = ------------ = 1.273

             pi

Since the area of the slice is A = (pi)(r^2), and since (d/2)^2 = r^2 = d^2/4

A =  (4 in^2) = (pi)(d^2 / 4)

Solving for d^2, we divide both sides by pi/4, obtaining:

4 in^2

---------- = d^2  = 5.093 in^2

 pi/4

and so d = √5.093 = 2.26 in (to the nearest 100th)

7 0
3 years ago
When the cost of a car is multiplied by 0.07 the result is ​$1760 . find the cost of the car.?
satela [25.4K]
1760 divided by 0.07 = the cost
So the answer is 25142 (rounded)





8 0
3 years ago
Read 2 more answers
6. A piece of carpet is 240cm long.
Anastaziya [24]

Answer:

150 cm.

Step-by-step explanation:

The number of parts = 1 + 2 + 5 = 8 so:

the largest part = 5/8 * 240

= 5 * 30

= 150 cm.

8 0
2 years ago
Other questions:
  • P(x) is a ploynomial. Here are a few values of P(x). P(-5)=-2 and P(5)=-1 What is the remainder when P(x) is divided by (x+5) WI
    8·2 answers
  • A farmer is enclosing a rectangular area for a pigpen. He wants the length of the pen to be 15 Ft longer then the width. The far
    11·1 answer
  • of a parabolic arch and is to have a span of 100 feet. The height of the arch a distance of 40 feet from the center is to be 10
    14·1 answer
  • What the answer asap
    5·2 answers
  • Help.............plz........thx
    14·1 answer
  • A to the power of 0 multiply by A to the power of 6
    11·2 answers
  • The interior angles of a triangle have measures kº, 27°, and 10°<br> What is the value of k?
    5·1 answer
  • Help please. i am desperate
    9·1 answer
  • Scott is using a 12 foot ramp to help load furniture into the back of a moving truck if the back of the truck is 3.5 feet from t
    10·1 answer
  • 7.2 is 250% of what number
    12·2 answers
Add answer
Login
Not registered? Fast signup
Signup
Login Signup
Ask question!